Contributions of humanitarian operations for national security: a perspective of the Brazilian Armed Forces action in three cases - Cunha, Luiza Ribeiro Alves; de Brito Junior, Irineu [UNESP]; Yoshizaki, Hugo Tsugunobu Yoshida; Fontainha, Tharcisio Cotta (FapUNIFESP (SciELO), 2024)
Paper aims: Disasters mark the last century’s history, impacting society’s security. In Brazil, National Security is defined as the condition that allows preserving territorial integrity and ensure citizens the exercise of constitutional rights and duties. Amid this scenario, this research aims to analyze how operations performed by the Brazilian Armed Forces in national disaster cases contribute to restoring national security. Originality: The originality of the research concerns the topic covered - national security based on a military vision - and the combination of methods used for analysis. Research method: For developing the research, scoping review, system thinking, and system dynamics methodologies are employed. Main findings: Two hypotheses were raised regarding the employment of military forces in humanitarian operations aimed at national security, considering proactive and reactive strategies. The hypotheses were analyzed and discussed through the development of simulation models. Furthermore, based on the readings, a new aspect of national security – besides preserving territorial integrity and ensuring the exercise of constitutional rights and duties - was raised: power projection by the demonstration of capabilities. Implications for theory and practice: The research has implications for academia as it presents a taxonomy of research aimed at national humanitarian operations, raises hypotheses aimed at national security, and validates them using simulation models. In practice, our results encourage the implementation of strategies to minimize and manage the impacts of disasters.
Keywords: Armed Forces; Disaster; Humanitarian operations; National security; Systems dynamics